2020
DOI: 10.3390/molecules25071559
|View full text |Cite
|
Sign up to set email alerts
|

Solubility, Hansen Solubility Parameters and Thermodynamic Behavior of Emtricitabine in Various (Polyethylene Glycol-400 + Water) Mixtures: Computational Modeling and Thermodynamics

Abstract: This study was aimed to find out the solubility, thermodynamic behavior, Hansen solubility parameters and molecular interactions of an antiviral drug emtricitabine (ECT) in various “[polyethylene glycol-400 (PEG-400) + water]” mixtures. The solubility of ECT in mole fraction was determined at “T = 298.2 to 318.2 K” and “p = 0.1 MPa” using an isothermal method. The experimental solubilities of ECT in mole fraction were validated and correlated using various computational models which includes “Van’t Hoff, Apelb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…The DSC curves and various thermal parameters (i.e., T fus , ∆ H fus and ∆ C p ) of pure and equilibrated ECT were not varied significantly ( p > 0.05), suggesting that ECT exists in pure crystalline form which was not transformed into polymorphs/hydrates/solvates after solubility experiments [ 18 , 20 ]. In addition, the X-ray diffraction (XRD) patterns of pure and equilibrated ECT were also found to be similar in our previous publication [ 16 ]. Hence, the DSC spectra of present study and XRD patterns of our previous publication suggested no transformation of ECT into different forms.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The DSC curves and various thermal parameters (i.e., T fus , ∆ H fus and ∆ C p ) of pure and equilibrated ECT were not varied significantly ( p > 0.05), suggesting that ECT exists in pure crystalline form which was not transformed into polymorphs/hydrates/solvates after solubility experiments [ 18 , 20 ]. In addition, the X-ray diffraction (XRD) patterns of pure and equilibrated ECT were also found to be similar in our previous publication [ 16 ]. Hence, the DSC spectra of present study and XRD patterns of our previous publication suggested no transformation of ECT into different forms.…”
Section: Resultssupporting
confidence: 80%
“…The solubility of ECT in water at T = 298.2 K is reported elsewhere [ 2 ]. The mole fraction solubility values of ECT in water, PEG-400 and various (PEG-400 + water) mixtures at T = 298.2 K to 318.2 K and p = 0.1 MPa have also been reported in our previous article [ 16 ]. However, the quantitative solubility values of ECT in other investigated PS are not reported elsewhere.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, HSPs for PPN, pure THP, pure water and various “THP + water” mixtures free of PPN were computed in this research. The δ value for PPN, pure THP and pure water was computed by applying Equation (3) [ 49 , 51 , 52 ] as follows: in which “ δ = total HSP; δ d = dispersion HSP; δ p = polar HSP and δ h = hydrogen-bonded HSP”. The HSPs for PPN, pure THP and pure water were estimated using “HSPiP software (version 4.1.07, Louisville, KY, USA)” [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, HSPs for PPN, pure THP, pure water and various "THP + water" mixtures free of PPN were computed in this research. The δ value for PPN, pure THP and pure water was computed by applying Equation (3) [49,51,52] as follows:…”
Section: Computation Of Hspsmentioning
confidence: 99%